Transformasi Digital SMK dengan E-Learning Moodle Plus: Inovasi Pembelajaran yang Mengintegrasikan Kolaborasi Orang Tua - Romadhon, Muhammad Imron; Qomariyah, Nur; Pratama, Krisna Raditya; Septiyanti, Nisa Dwi (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
Digital transformation in Vocational High Schools (SMK) faces significant challenges, particularly the dominance of traditional teaching methods and the limited involvement of parents in the learning process. This study aims to develop a Moodle Plus–based e-learning platform integrated with parental involvement as supervisory partners, and to evaluate its validity, practicality, and effectiveness. The research employed a Research and Development (R&D) approach using the plomp model, which consists of preliminary investigation, prototype development, and assessment phases. The trial involved 31 tenth-grade students at SMKN 2 Yogyakarta, adopting a One-Group Pretest–Posttest design. The validity of the e-learning platform was assessed using ISO 25010 standards, focusing on functionality, usability, and portability. Effectiveness was measured by comparing pretest and posttest results through the Wilcoxon test. The findings indicate thatthe Moodle Plus–based e-learning platform is valid, with product moment correlation values of r = 1 for functionality and portability (excellent) and r = 0.607 for usability (good). The Wilcoxon test produced a significance value of 0.000 (< 0.05), demonstrating a substantial improvement in students’ psychomotor learning outcomes after using the platform. In conclusion, Moodle Plus e-learning, supported by parental involvement as supervisory partners, is proven to be valid, practical, and effective, making it feasible for implementation as a Learning Management System in vocational schools.Keywords: e-learning, moodle plus, ISO 25010, parental collaboration